Step 1: Simplify both sides of the equation by using the distributive property.
5(x+3) becomes 5x + 15 and -7(x-4) becomes -7x + 28.
The equation becomes 5x + 15 - 7x + 28 = 38.
Step 2: Combine like terms.
5x and -7x are like terms that can be combined.
5x - 7x becomes -2x.
The equation becomes -2x + 15 + 28 = 38.
Step 3: Simplify further by combining like terms on the left side of the equation.
-2x + 15 + 28 becomes -2x + 43.
The equation becomes -2x + 43 = 38.
Step 4: Isolate the variable by subtracting 43 from both sides of the equation.
-2x + 43 - 43 = 38 - 43.
-2x = -5.
Step 5: Solve for x by dividing both sides of the equation by -2.
-2x/-2 = -5/-2.
x = (-5)/(-2).
x = 2.5.
The solution to the equation 5(x+3)-7(x-4)=38 is x = 2.5.
you have been given the following equation to solve as a challenge by your friend, create a list of steps that you follow to find the solution
5(x+3)-7(x-4)=38
1 answer